Demographic and clinical characteristics of chronic myeloid leukemia patients: A study on confined populations of Southern India - Manjula Gorre; R B Sashidhar; Sandhya Annamaneni; Raghunadharao Digumarti; Vishnupriya Satti (Indian Journal of Medical and Paediatric Oncology)
Context: Chronic myeloid leukemia (CML) is one of the most common hematological malignancies in all populations throughout the world. Even though the pathophysiology of CML was well explained in majority of the studies, the incidence of CML was shown to exhibit population diversity, and hence, the demographic factors underlying CML origin remain to be understood. Further, the introduction of tyrosine kinase inhibitors had revolutionized the treatment of CML over the years; however, there is a need for developing tailoring therapy to individual risk since the patient clinical heterogeneity poses a major problem during drug response. Therefore, the study of basic clinical picture may aid in planning treatment strategies for CML patients. Aim: The aim of this article is to study the epidemiological and clinical variables associated with the prognosis of CML. Subjects and Methods: We have considered the distribution of various demographic and clinical variables among 476 CML patients diagnosed at Nizam's Institute of Medical Sciences, Hyderabad, Telangana, India. Statistical Analysis Used: All the analyses were performed through SPSS software (version 21.0). Correlation and Cox regression analyses were also performed. Results: Apart from the elevated male sex ratio in CML incidence, high frequency of males was observed to be nonresponders to imatinib mesylate (IM). IM response was shown to be dependent on phase of diagnosis, whereas overall survival of CML patients depends on the age at onset and response to IM. Conclusions: The study of epidemiology and clinical picture of CML patients may help in planning better treatment strategies at diagnosis to achieve long-term progression-free survival.